CONCEPTUAL ANALYSIS OF THE MONTESSORI MODEL IN THE DEVELOPMENT OF DAYCARE PROGRAM QUALITY - Desy Suciati, Romadona; Dwi Saputro, Anip; Harmanto, Bambang (EDUPEDIA, 2025)
This research intends to conceptually examine the Montessori Model and its role in enhancing the quality of daycare programs, specifically its application in Pocenter Playgroup, Ponorogo. Employing a descriptive qualitative approach, the study gathered data via direct observation of educational activities, comprehensive interviews with parents and teachers, and documentation of routine learning records and children’s portfolios. The results indicate that the organized environment, access to multisensory resources, and the combination of sensory and practical life activities are central to Montessori practices within the daycare environment. These activities promote children’s autonomy, focus, imagination, and self-control, while also enhancing fine-motor skills and social-emotional abilities. Interactions between teachers and children demonstrate educators' roles as facilitators and observers, enabling children to actively explore and engage with tangible materials suited to their developmental stages. Genuine assessment via portfolios and daily records improves communication with parents and guarantees ongoing stimulation between home and school. The research highlights various challenges, such as differences in teacher proficiency, scarce access to quality Montessori materials, and the necessity for improved assessment instruments. In summary, the results highlight that the Montessori Model provides an extensive conceptual foundation that greatly enhances the quality of daycare programs when applied consistently and backed by proper teacher training, oversight, and contextual adjustment. This research emphasizes the significance of combining conceptual comprehension, teaching methods, and program assessment to enhance early childhood education services in daycare environments.